THE STORIES OF MARRIAGE (Journal of Law and Family Studies; Vol 12 No 1 (2010), 2010)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The gay and lesbian community's response to California's Proposition 8 was strong and quick. Within days of the 2008 election, opponents of the measure had targeted its proponents, in particular the Mormon Church, as subjects for scorn. Singling out the Mormon Church on this issue was particularly ironic because to the extent that members of the Mormon Church were responsible for the success of Proposition 8, they simply did to the gay community what courts of the United States consistently did to their forebears: defined away their right to marry. In striking down individuals' rights to enter into polygamous marriages, courts said that polygamy was not marriage and that monogamy was marriage, but they expended little energy explaining why. This article does not condone either the forceful effort to pass Proposition 8 or the counter-response from the gay community, but it will argue that part of the problem that same-sex marriage ("SSM") advocates encounter stems from the failure of courts to explain what marriage is. It is very hard to talk about a right to marry without a common understanding of why states license marriage. In the end, this article will offer a definition of marriage which suggests that marriage can be beneficial to the state, beneficial to the couple, and integrated into the rich social history of marriage without necessarily being gendered. In order to understand why this proffered story is important, the article first evaluates the marriage narratives that have been told to date in the SSM debate and shows how those stories have fared as constitutional claims.